Bioenergetic reprogramming of macrophages reduces drug tolerance in Mycobacterium tuberculosis - Yadav, Vikas; Sahoo, Sarthak; Malhotra, Nitish; Mishra, Richa; Sreedharan, Sreesa; Rajmani, Raju S.; Shanmugam, Siva; Shandil, Radha K.; Narayanan, Shridhar; Thacker, Vivek Vijay; Laxman, Sunil; Jolly, Mohit Kumar; et al. (Nature Communications, 2025)
Effective clearance of Mycobacterium tuberculosis (Mtb) requires targeting drug-tolerant populations within host macrophages. Here, we show that macrophage metabolic states govern redox heterogeneity and drug response in intracellular Mtb. Using a redox-sensitive fluorescent reporter (Mrx1-roGFP2), flow cytometry, and transcriptomics, we found that macrophages with high oxidative phosphorylation (OXPHOS) and low glycolysis harbor reductive, drug-tolerant Mtb, whereas glycolytically active macrophages generate mitochondrial ROS via reverse electron transport, imposing oxidative stress on Mtb and enhancing drug efficacy. Computational and genetic analyses identified NRF2 as a key regulator linking host metabolism to bacterial redox state and drug tolerance. Pharmacological reprogramming of macrophages with the FDA-approved drug meclizine (MEC) shifted metabolism towards glycolysis, suppressed redox heterogeneity, and reduced Mtb drug tolerance in macrophages and mice. MEC exhibited no adverse interactions with frontline anti-TB drugs. These findings demonstrate the therapeutic potential of host metabolic reprogramming to overcome Mtb drug tolerance.